2019
DOI: 10.1080/25765299.2019.1687396
|View full text |Cite
|
Sign up to set email alerts
|

Growing energy demand in the GCC countries

Abstract: The energy sector in GCC countries plays a vital role in achieving economic and social development and contributing to the Gross Domestic Product (GDP). Furthermore, the energy sector plays a major role in meeting the water and food needs in these countries that have harsh climate conditions and water scarcity. However, the consumption of energy is high in the GCC relative to other developed countries and this is one of the key challenges faced by the GCC. Growing energy consumption will threaten exports, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…According to a study conducted by Bhutto et al [45] in 2014, the transfer to renewable energy technology would reduce fossil fuel consumption in GCC countries and address their environmental challenges [46]. The population growth and brisk economic expansion in the region, which is linked to the growth of energy-intensive industries such as petrochemical, aluminum and steel industries, led to increasing electricity consumption [45].…”
Section: Renewable Energy Implementationmentioning
confidence: 99%
“…According to a study conducted by Bhutto et al [45] in 2014, the transfer to renewable energy technology would reduce fossil fuel consumption in GCC countries and address their environmental challenges [46]. The population growth and brisk economic expansion in the region, which is linked to the growth of energy-intensive industries such as petrochemical, aluminum and steel industries, led to increasing electricity consumption [45].…”
Section: Renewable Energy Implementationmentioning
confidence: 99%
“…Electricity used to power residential and commercial buildings accounts for more than 70 percent of the total electricity consumed in the UAE today (Lin, Afshari, and Azar, 2018). The peak demand in the summer, due to increasing rates of space cooling, is often twice the off‐peak summer consumption and three times the peak winter consumption (Al‐Badi and AlMubarak, 2019:489). Authorities have set an ambitious target of reducing residential and corporate electricity consumption by 40 percent as part of the demand‐side management initiative, which is designed to encourage consumers to optimize their energy use.…”
Section: Recipe For Success: Energy Reformsmentioning
confidence: 99%
“…Data regarding the energy required for wastewater treatment in the UAE is unavailable. According to some international estimates, the energy intensity of primary treatment is 0.1-0.3 KWh/m 3 , and for secondary treatment, the estimate ranges between 0.275 and 0.59 KWh/m 3 [44]. It is imperative to note that since water and energy are mostly produced in co-generation plants, as in many desert regions, proactively considering this fact of the nexus in the sustainability rating systems would also facilitate financial and economical savings.…”
Section: Status Of Water and Energy Consumption Of Uaementioning
confidence: 99%
“…The United Arab Emirates (UAE), similar to many fast-growing economies, has been indexed as one of the countries producing the highest carbon footprints in the world [1,2]. Researchers have revealed that electricity consumption has doubled in the last ten years, and the main contributing factor to this surge is attributed to rapid urbanization, population, and economic growth in the country [3]. Energy consumption has been increasing at an annual rate of 4% and has reached 5% in 2020.…”
Section: Introductionmentioning
confidence: 99%